Pengaruh Disclosure dan Manajemen Laba terhadap Cost of Capital - Tri Kurniawati; Nadia Ayu Rifani Putri (Universitas Negeri Padang, 2020)
This study is aimed to analyze the influence of disclosure and earnings management on cost of capital. The population of this study is the real estate companies which is listed at the Indonesia Stock Exchange (IDX) and the sample is determined by purposive sampling. The samples consist of 28 companies in 2013-2015. Disclosure is measured by Disclosure Index, earnings management is measured by discretionary accrualls and cost of capital is estimated by EBO model. The research hypotheses are tested by using multiple regression. The results of this research indicate that (1) disclosure has no significant influence on the cost of capital, and (2) earnings management has positive and significant influence on cost of capital.